Inflammatory protein serum amyloid A1 marks a subset of conventional renal cell carcinomas with fatal outcome - Paret, Claudia; Schön, Zorica; Szponar, Adrianna; Kovacs, Gyula (European urology, 2010)
Background - Conventional renal cell carcinoma (RCC) is the most common renal cancer. As the metastatic conventional RCC is practically incurable, there is a need for markers to estimate the tumour aggressiveness. - Objective - To identify and characterise new marker(s) associated with the poor prognosis of conventional RCC. - Design, Setting, and Participants - RNA from 24 conventional RCCs was analysed for global gene expression by Affymetrix U133 Plus 2.0 arrays. Tissue microarrays containing 224 renal tumours including 87 conventional RCCs were used for immunohistochemistry. Cell lines HD2, HD48, HA344 and HA465 established in our laboratory were used for invasion assay and zymography. - Measurements - Serum amyloid A 1 (SAA1) was found to be upregulated in conventional RCCs and it has been analysed by quantitative RT-PCR and immunohistochemistry on TMAs to establish the correlation between SAA1 protein expression and patient survival by uni and multivariate analysis. The effect of SAA1 on tumour cell behaviour in vitro has also been examined by invasion assay and zymography. - Results and Limitations - SAA1 RNA is expressed in conventional RCC samples of patients with poor prognosis. Immunohistochemistry of 72 conventional RCCs with a 5 yr follow up showed a correlation between SAA1 expression and the clinical outcome of disease. Stimulation of conventional RCC cell lines with recombinant SAA1 increased the expression of metalloproteinase (MMP)-9 and the invasive potential of tumour cells. Limitation of the study is a relatively small number (72) of patients having follow up. - Conclusion - SAA1 seems to be a useful marker to estimate the prognosis of conventional RCCs.
Online verfügbar 27 August 2009
Gesehen am 26.06.2023